Laparascopic Management of Peptic Ulcer Perforation: Initial Experience in Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2011)
Key Words: laparoscopic repair; early return to work; peptic ulcer performationDOI: 10.3329/jcmcta.v21i2.7731 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):16-20